HELP for the future: fairer repayment of student debt - Norton, Andrew; Cherastidtham, Ittima (Grattan Institute, 2016)
Reducing the thresholds at which former students repay their debt to the Higher Education Loan Program would increase repayments by an initial $500 million a year and more over time. Without change, HELP costs will soar, putting teaching and research at risk of cuts.
Keywords: Education and Training -- Costs; Learning, education and training; Education and Training; Costs; Learning, education and training